Autonomous Self-evolution of AI on drones: Transfer Learning of Neural Architecture Search’s brain - Rajagopal , A; Nirmala, V (International Journal of Computer Sciences and Engineering, 2019)
Biological creations adapt to environmental changes. Similarly, can autonomous AI system adapt to the environmental changes? During natural disasters such as floods or cyclones, an autonomous robot might unexpectedly face new conditions such as occlusions from dust, and hence may need to adapt itself. Is it possible for a drone flying into a disaster zone to autonomously evolve itself without any human guidance. Many times autonomous AI systems may be exposed to new conditions that it hasn’t yet been trained. How to provision full autonomy to such autonomous AI?. This is the challenge this paper answers. Disruptions in internet connectivity during disasters add an additional dimension to this challenge. How does the AI on drone self-adapt during disasters? Is it possible to employ Neural Architecture Search (NAS) for autonomously evolving the drone’s intelligence to the new environment?. With internet outages during disasters, is it possible to evolve the AI by evolving the model locally on the drone?. In short, this paper explores how to design autonomous drones that can triumph over disasters, by autonomous evolving the drone intelligence to the new environment using NAS.